Buying up the block: An experimental investigation of capturing economic rents through sequential negotiations. - Goswani, G; Noe, T; Wang, J (Oxford Finance, 2008)
This paper develops and experimentally implements a simple multi-negotiation bargaining game, in which one agent, called the “developer,” must reach agreements with a series of other agents, called “landowners,” in order to implement a valueincreasing project. The game has a unique subgame perfect Nash equilibrium under which the surplus from the project is split between the landowner and developer without any dissipation of value. In the actual experiments, however, on average almost half of the value of the project was dissipated. The costs of dissipation fell disproportionately on the developer, who was able to capture less than 5% of the value generated by the project. The results of this experiment call into question the ability of private negotiations between a large number of parties, even in a world without explicit contracting costs, to induce Pareto-optimal allocations of property rights.